LITHOFACIAL COMPOSITION AND DISTRIBUTION OF MIDDLE ALBIAN STRATA WITHIN THE CRIMEAN PLAINS - Kyselevych, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Middle Albian sedimentary complex is deposited on Middle Albian rocks, commonly with no evident unconformity, and includes, along with sedimentary rocks, volcanic activity products. Middlle Albian sediments are distributed almost everywhere within the North Crimean paleodepression. They occur at a depth of 2-5 km and are represented by sedimentary-volcanogenic formations whose generation was caused by intense activity of 6 stratovolcanoes and 3 shield volcanoes. Such formations fail to occur only on a few local sites of the paleodepression and in its northern nearside zone. Sediments are characterized by wide development in their section, along with sedimentary rocks, of pyroclastic and effusive formations whose generation was caused by volcanic activity. The volcanic activity was at its highest during the Middle Albian, which resulted in accumulations of facies-variable volcanogenic-sedimentary strata. Volcanogenic and volcanogeno-clastic Middle Albian sediments occur among marine clay formations as lens-shaped bodies, sheets and flows sometimes stretching over dozens of kilometers, their thickness ranging from a few metres to hundreds. Structural features of volcanogenicsedimentary strata of different regions depend on their proximity to the centers of volcanic activity and are determined by the nature and characteristics of paleovolcanic eruptions. A closer proximity to paleovolcanoes accounts for an increase in volcanic rocks in the section, with effusive rocks being mostly abundant among them. At a longer distance from the centers of volcanic activity, pyroclastic, volcanogenicsedimentary and sedimentary deposits become more abundant in the section. Synthesis and analysis of the lithological and petrographic characteristics of Middle Albian sediments, which were based on analyzing deep parametrical and exploration drilling data, made it possible to define 10 main Middle Albian types of lithofacies. These differ in their composition and the share of volcanic activity products found in marine clay sediments. Lithological-facies types of the Middle Albian sediment sections have been defined, as well as the limits of their lateral distribution within the North Crimean paleodepression of the Crimean plains.
Keywords: lithofacial composition; middle albian strata; petrography